Use of the BSI Indicator for Dry Hot Season Items for July in Wasit Governorate for the Period (1984-2022) - Taraf Razaq Al-Quraishi , Star; Dr. Malik Nasir Aboud (Journal of College of Education, 2024)
Using the Bare Soil Index (BSI) to identify the probability of erosion of soil in the central governorate of Iraq, derived from satellite imagery and geospatial information from various sources in the GIS environment (GIS) By integrating the space image with the BSI map the erosion of the natural soil of the study area, an indicator of the causes of soil erosion was obtained among the most important forms of climate change with social and economic repercussions worldwide, the study aims to analyze satellite imagery (Landsat 8.7.5 For space data to predict soil erosion index levels and study years (1984, 1989, 1994, 1999, 2004, 2009, 2014, 2019, 2022). The indicator’s categories are divided into three categories: High erosion, medium erosion, and erosion-free, showing the results of the 2004 high erosion class with an area of the highest percentage (73.90%), the lowest area (5,531 km2) in 1999, is 13,068 km2. At 31.28%, the average erosion rate was the highest in 2019. (9809) km2, representing (55.47) %, and the lowest area recorded for 2009, reaching (3914) km2, at 22.13%, while the erosion-free item occupied the highest area in 1989 reaching (2773) km2, with a ratio of 15.51%, and the lowest area recorded in 2004 to reach an area of (702 km2), land degradation has undergone significant changes in the past years in Wasit governorate; This is the result of continuous land expansion and soil drift